Sexual Assault in Canada Law, Legal Practice and Women's Activism - A. Sheehy, Elizabeth (University of Ottawa Press / Les Presses de l'Université d'Ottawa, 2012)
"Sexual Assault in Canada" is the first English-language book in almost two decades to assess the state of sexual assault law and legal practice in Canada. Gathering together feminist scholars, lawyers, activists and policy-makers, it presents a picture of the difficult issues that Canadian women face when reporting and prosecuting sexual violence. The volume addresses many themes including the systematic undermining of women who have been sexually assaulted, the experiences of marginalized women, and the role of women's activism. It explores sexual assault in various contexts, including professional sports, the doctor-patient relationship, and residential schools. And it highlights the influence of certain players in the reporting and litigation of sexual violence, including health care providers, social workers, police, lawyers and judges. "Sexual Assault in Canada" provides both a multi-faceted assessment of the progress of feminist reforms to Canadian sexual assault law and practice, and articulates a myriad of new ideas, proposed changes to law, and inspired activist strategies.